ANALISIS PERUBAHAN PERILAKU TOKOH UTAMA NOVEL BELENGGU ILSE KARYA RUWI MEITA : KAJIAN PSIKOLOGI SASTRA - Santika Ayu Sastrawati; Ida Bagus Jelatik; I Ketut Nama (Cahaya Ilmu Bangsa Institute, 2023)
This research aims to describe changes in the behavior of the main character in the novel Belenggu Ilse by Ruwi Meita. The theory used in this paper is the psychological theory of behaviorism. The method used in this research is literature study with the research techniques of reading, listening and taking notes. Based on research results, the main character in the novel BI receives several stimuli that can change his personality. The simulation is a simulation provided by the Minos.com admin and a simulation provided by Firas, Ilse's husband. There are three simulations provided by the Minos.com admin, namely affective changes, psychomotor changes and cognitive behavioral changes.